Assessment of the Nutritional Value of Yellow Mealworm Cultivated on Fruit Waste - Tariq, Maria; Naima Din; Shamim Akhtar; Misbah Ashraf; Ahmed, Mian Muhammad; Abbas, Sana; Ahmed, Bashir; Muhammad Adeel; Sarwar, Muhammad Anas; Khan, Mehboob; Ali, Ahmed (Indus Journal of Bioscience Research, 2025)
Poultry meat is the inexpensive sources of protein for the humans. Poultry meat acceptability always depends on meat quality. Cereals, fishmeal, soybean are commonly used protein sources for Poultry Protein is major nutrient costing higher value compared to other ingredients. worms can be used as protein source because of limited resources. One such is the insect meal, which has come up as an alternative feed for poultry. This also improves the quality and taste of poultry meat which is desired by many people. The study involved rearing of fresh and dried mealworm (Tenebrio molitor) on fruit waste and their nutritional value will be analyzed. Mealworms are easy to breed and do not require large area for production. Therefore, yellow mealworm (Tenebrio molitor) meal can serve as a dietary protein in meat type poultry. This is because larvae of Tenebrio molitor (mealworms) are highly nutritious, containing high levels of protein and lipids. Using fruit waste is better means for confronting with waste pollution because it is a cheap and excellent organic material. An essential aspect involves understanding the nutritional profile of mealworms raised on fruit waste, and subsequent tests are performed to comprehensively evaluate their characteristics. However, further research is needed to explore the possibility of using mealworms as an alternative protein source to soybean, potentially reducing feed costs without compromising bird performance. T. molitor larvae show promise as a poultry protein source, but challenges include toxin mitigation, consumer acceptance, and pricing. Careful consideration of nutrition, biosafety, and market factors is needed for widespread adoption.